Molecular Identification of Endophytic Fungi from Banana Leaves (Musa spp.) - Latiffah Zakaria; Wan Nuraini Wan Aziz (Tropical Life Sciences Research, 2018)
Endophytic fungi are part of microbial community found in various types of plant tissues including the leave, and display a range of symbiotic interactions with the plant host. In this study, endophytic fungi isolated from banana leaves were identified using ITS (Internal Transcribed Spacer region) sequences of which 10 genera comprising 17 species were molecularly identified. Endophytic fungal species identified were Nigrospora oryzae, Nigrospora sphaerica, Colletotrichum gloeosporioides, Colletotrichum siamense, Fusarium equiseti, Fusarium chlamydosporum, Phoma sorghina, Pestalotiopsis oxyanthi, Pestalotiopsis theae, Pestalotiopsis eugeniae, Penicillium steckii, Penicillium purpurogenum, Bipolaris papendorfii, Bipolaris sp., Lasidiodiplodia theobromae, Cochliobolus intermedius dan Aspergillus niger. The present study showed that several endophytic fungal genera/ species are common plant pathogen and there is a possibility that these endophytes can become pathogenic. Some of the fungal endophyte might be mutualist or saprophyte. Kulat endofitik merupakan sebahagian daripada komuniti mikrob dalam pelbagai jenis tisu tumbuhan termasuk daun, dan memaparkan pelbagai interaksi simbiotik dengan tumbuhan perumah. Dalam kajian ini, kulat endofitik dipencilkan daripada daun pisang, telah dikenal pasti menggunakan jujukan ITS (Kawasan Penjarak Dalaman) di mana 10 genus yang terdiri daripada 17 spesies telah dikenal pasti secara molekul. Spesies kulat endofitik yang dikenal pasti adalah Nigrospora oryzae, Nigrospora sphaerica, Colletotrichum gloeosporioides, Colletotrichum siamense, Fusarium equiseti, Fusarium chlamydosporum, Phoma sorghina, Pestalotiopsis oxyanthi, Pestalotiopsis theae, Pestalotiopsis eugeniae, Penicillium steckii, Penicillium purpurogenum, Bipolaris papendorfii, Bipolaris sp., Lasidiodiplodia theobromae, Cochliobolus intermedius dan Aspergillus niger. Kajian ini menunjukkan bahawa beberapa genus atau spesies kulat endofitik merupakan patogen tumbuhan yang lazim dan ada kemungkinan bahawa kulat endofitik ini boleh menjadi patogenik. Sebahagian kulat endofit ini mungkin mutualis atau saprofit.